Physician perspectives on pulmonary hypertension in ILD: results of a cases-based survey - Ho Cheol Kim; Christopher S. King; Christopher Thomas; Vikramjit Khangoora; Osman Malik; Jared Wilkinson; Shambhu Aryal; Anju Singhal; Alan Nyquist; Oksana A. Shlobin; Steven D. Nathan (BMC Pulmonary Medicine)
Abstract Background Pulmonary hypertension (PH) complicates the course of patients with interstitial lung disease (ILD) in 30–55% of cases and is associated with increased morbidity and mortality. The optimal timing of diagnostic right heart catheterization (RHC) and the impact of transthoracic echocardiographic (TTE) imaging on this decision remain uncertain. This study explores physician decision-making regarding PH suspicion in patients with ILD, and the necessity for TTE and RHC. Methods A case-based survey was conducted among physicians from diverse geographic and professional backgrounds. Participants assessed anonymized ILD cases, providing their clinical suspicion of PH and recommendations for TTE and then RHC both before and after receiving TTE results. Predictive accuracy for PH was compared to the FORD index, a validated scoring system. Results There were 10 cases provided, of which 3 had hemodynamically confirmed PH and 7 did not have PH. There were 42 respondents to the survey. Following the TTE results, the proportion of responses indicating high suspicion for PH increased in all PH cases and also increased in some non-PH cases. In PH cases, respondents accurately predicted mPAP ≥ 25 in 98.4% and PVR ≥ 3 Woods Units in 90.5% of responses, although only 24.6% and 20.6% matched the value ranges, respectively. In non-PH cases, mPAP < 25 and PVR < 3 Wood Units were correctly identified in 60.9% and 67.0% of responses, with 30% incorrectly predicting PH. Compared to the FORD index (sensitivity: 43.7%, specificity: 86.6%), respondents demonstrated higher sensitivity (88.9%) but lower specificity (70.1%) for PH diagnosis. Conclusions Physicians demonstrate high sensitivity but moderate specificity in predicting PH, both with and without TTE results. The FORD index had greater specificity and may serve as a complementary tool, reducing the need for unnecessary RHCs. Standardized protocols are needed to facilitate detection of PH while optimizing the timing of RHCs in ILD patients.